Las secuelas del exilio cubano: desterrados al fuego de Matías Montes Huidobro. - Jiménez, Luis A. (2012)
In this essay we discuss the sequelae experienced by the Cuban refuge in the United States. We analyze these consequences in terms of his cultural and linguistic identity, the psychological and existential effects as well as his way of dressing. Within this last section we examine the protagonist-narrator?s overcoat, since this garment becomes the leit-motif of the novel and without the vestiment Montes Huidobro?s text would not exist.